2010
DOI: 10.1242/jcs.067645
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 couples the insulin-like growth factor-1 receptor to inside-out integrin activation

Abstract: SummarySyndecan-1 (Sdc1) engages and activates the avb3 (and/or avb5) integrin when clustered in human carcinoma and endothelial cells. Although the engagement is extracellular, the activation mechanism is cytoplasmic. This talin-dependent, inside-out signaling pathway is activated downstream of the insulin-like growth factor-1 receptor (IGF1R), whose kinase activity is triggered by Sdc1 clustering. In vitro binding assays using purified receptors suggest that association of the Sdc1 ectodomain with the integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
144
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(151 citation statements)
references
References 111 publications
(133 reference statements)
7
144
0
Order By: Relevance
“…While integrins have been shown to associate with SYNDECAN-1 AND WOUND HEALING numerous kinases, including FAK and epidermal growth factor receptor (EGFR), thus far, sdc1 has only been shown to associate directly with the insulin-like growth factor 1 receptor (IGF1R); along with a v -containing integrin heterodimers, sdc1 and IGF1R form a ternary complex that induces cell signaling. 46 Association between sdc2 and integrin is more complex. A juxtamembrane sequence on the C1 domain of sdc2 associates with the integral membrane tyrosine phosphatase, CD148, which in turn associates with b 1 -family integrins.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While integrins have been shown to associate with SYNDECAN-1 AND WOUND HEALING numerous kinases, including FAK and epidermal growth factor receptor (EGFR), thus far, sdc1 has only been shown to associate directly with the insulin-like growth factor 1 receptor (IGF1R); along with a v -containing integrin heterodimers, sdc1 and IGF1R form a ternary complex that induces cell signaling. 46 Association between sdc2 and integrin is more complex. A juxtamembrane sequence on the C1 domain of sdc2 associates with the integral membrane tyrosine phosphatase, CD148, which in turn associates with b 1 -family integrins.…”
mentioning
confidence: 99%
“…This lead to the characterization of synstatin, a sdc1-derived peptide that binds to integrins and reduces cancer cell invasion and tumor angiogenesis. 45,46,55 Sdc1-mediated activation of integrins impacts wound healing. Corneal wound healing studies performed using sdc1-null mice show delayed reepithelialization not caused by altered cell proliferation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been found that syndecan-1 interacts with IGF-1 receptor to activate integrin (Beauvais and Rapraeger, 2010). It is reasonable to speculate insulin on cancer cell proliferation in vivo may involve an indirect mechanism, such as IGF-1 stimulation.…”
Section: Insulin Like Growth Factor and Cancermentioning
confidence: 99%
“…Thus the syndecans involve in synchronized expression patterns during embryogenesis and malignant transformation. These cell-cell interactions via their extracellular matrix ligands control cell proliferation, dynamic cytoskeletal remodeling, apoptosis and gene expression.Over the last few years, it has been widely accepted that heparan sulfate proteoglycans play a role in growth control, cell spreading, cellular recognition, cellular adhesion, and signaling, possibly as co -receptors with integrins, IGF-1R and cell -cell adhesion molecules, including fi bronectin, vitronectin, laminins, and the fi brillar collagens (Bernfi eld et al, 1999;Woods, 2001;Alexopoulou et al, 2007;Beauvais and Rapraeger, 2010). In addition, all syndecans have dibasic peptide sequence adjacent to the plasma membrane.…”
mentioning
confidence: 99%